Effects of Collision Damage on the Ultimate Strength of FPSO Vessels - Alie, Muhammad Zubair Muis; Ramasari, Dian; Rachman, Taufiqur; Adiputra, Ristiyanto (UI Scholars Hub, 2020)
Floating production storage offloading (FPSO) vessels are movable offshore structures. These structures are designed with large dimensions, and their decks are loaded with several types of equipment. During collision damage, the hull and deck parts loaded with equipment are severely affected. Therefore, the ultimate strength of FPSO vessels should be thoroughly checked and evaluated. The objective of the present study is to analyze the ultimate strength of FPSO vessels against collision damage characterized by hogging and sagging under longitudinal bending. The cross section of an FPSO vessel is modeled with elements composed of stiffened and unstiffened plates. The vessel length is assumed to occupy one frame space. The ultimate strength of FPSO vessels against collision damage is determined by performing a numerical analysis under hogging and sagging conditions. Multipoint constraint is applied to both sides of the cross section, and the material properties are set to be constant. Collision damage is represented by the loss of element stiffness, and it represents the percentage of the ship’s depth. For the extent of transversal damage, B/16 is set to be constant. The minimum and maximum collision damages are taken as 10% and 60% of the ship’s depth, respectively. Numerical results show that the ultimate strength of FPSO vessels and their bending stiffness decrease under collision.